Systematic Review and Quality Evaluation of Pharmacoeconomic Studies on Traditional Chinese Medicines - Yang, Nan; Zhang, Huihui; Deng, Taoyi; Guo, Jeff Jianfei; Hu, Ming (Frontiers in Public Health, 2021)
Objectives: This study was aimed to describe the currently published pharmacoeconomic researches on Traditional Chinese Medicine (TCM), evaluate the quality of the studies to analyze existing issues and make suggestions for improvement. Methods: We developed the search strategy, set inclusion and exclusion criteria and searched the articles of pharmacoeconomic studies on TCM from eight Chinese and English databases from inception to April 2020, including China National Knowledge Infrastructure, Chongqing VIP Information, WANFANG Database, Sinomed, Pubmed, Embase, and Cochrane Library. A total of 431 published pharmacoeconomics studies were identified and included for this study including cost-effectiveness, cost-benefit, cost-minimization, cost-utility or combination analyses. Basic information of the literatures and key pharmacoeconomic items of each study were extracted. Then quality of the studies was evaluated by using economic submissions checklist of British Medical Journal for authors and peer reviewers, such as study design, research time horizon, sample size, perspective, evaluation methods. Results: Of 431 TCM pharmacoeconomic research articles, there were 424 Chinese articles and 7 English articles. These studies evaluated the economy of 264 Chinese patent medicines and 70 kinds of TCM prescriptions for 143 diseases, such as central nervous, cardiovascular, respiratory, gynecology, etc. Study TCMs included blood-activating agents (e.g. Xuesaitong tablet, Fufant Danshen tablet, Danhong Injection), blood circulation promoting agents (e.g. Shuxuetong injection, Rupixiao tablet, Fufang Danshen injection), and other therapeutic agents. The overall quality score of the studies was 0.62 according to economic submissions checklist of British Medical Journal for authors and peer reviewers. The highest mark was 0.85 and the lowest mark was 0.38. The average quality score of studies in English was 0.72, which was higher than that of studies in Chinese with 0.62. Conclusions: Quality of pharmacoeconomic studies on TCM was relatively, generally low. Major concerns included study design, inappropriate pharmacoeconomic evaluation, insufficient sample size or non-scientific assessment. It is warrant to strengthen methodological training and cooperation, conform special pharmacoeconomic evaluation guideline, and propose reasonable health outcome index.